2023
DOI: 10.1039/d3sc02298f
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective heat boosting electrochemiluminescence for single cell imaging

Abstract: In operando visualization of local electrochemical reactions provides mechanical insights into the dynamic transport of interfacial charge and reactant/product. Electrochemiluminescence is a crossover technique that quantitatively determines faraday current and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Gou et al addressed this issue by accelerating the reaction rate and enhancing thermal convection of the ECL process through a photothermal effect. [76] This advancement led to a notable 20-fold increase in signal contrast for ECL cell imaging, offering an effective solution to the weak light emission issue. In the abovedescribed works, ECL labels were required for successful visualization.…”
Section: Ecl Microscopy Of Biological Entitiesmentioning
confidence: 99%
“…Gou et al addressed this issue by accelerating the reaction rate and enhancing thermal convection of the ECL process through a photothermal effect. [76] This advancement led to a notable 20-fold increase in signal contrast for ECL cell imaging, offering an effective solution to the weak light emission issue. In the abovedescribed works, ECL labels were required for successful visualization.…”
Section: Ecl Microscopy Of Biological Entitiesmentioning
confidence: 99%
“…11,12 Since ECL provides an optical readout, in the last decade, it has evolved into a powerful technique for microscopy applications, allowing for the study of micro/nanoparticles and biological entities such as cells or organelles. 13–23 Two main imaging approaches have been developed: (i) positive ECL (ECL+) with a light-emitting object, which directly generates ECL or is labeled with an ECL tag, on a dark background; and (ii) shadow or negative label-free ECL (ECL−), which is based on a non-ECL emissive object hindering the ECL reagents diffusion and thus shadowing the ECL background. 18,24 Both provide complementary information about the imaged object.…”
Section: Introductionmentioning
confidence: 99%
“…40–44 In addition, it was demonstrated that ECL can be performed under microscopy, 45–50 allowing the imaging of single micro- and nano-objects, 51–58 particularly those of biological interest. 59–70…”
Section: Introductionmentioning
confidence: 99%